Organic Vegetable Gardening in Florida - Danielle D. Treadwell; Sydney Park Brown; James Stephens; Susan Webb (EDIS)
Updated comprehensive guide written as a companion to the Florida Vegetable Gardening Guide. It is intended for the home gardener who prefers to use natural and organic materials as well as methods that are compatible with the philosophy of organic gardening.